Dapitan prose (literary folio) (Espaa, Manila : UST Publishing House)
1. Prose--periodicals.
Filipino and English text . Dapitan is the official Literary Folio of the Flame, The UST Student publication of Faculty of Arts and Letters.
Basic ed. students